Correction: Liu et al. Relationships between Grey Matter Volume in the Bilateral Superior Frontal Gyrus and Reactive Aggression Varied by Level of Traditional Masculinity. Brain Sci. 2024, 14, 605 - Weijun Liu; Cody Ding; Ziang Li; Hong Chen (Brain Sciences)
There is a typographical error in the description of participant demographics in the original publication [...]